2001
DOI: 10.1007/s102270000022
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus in Dermatology

Abstract: There are case reports of pyoderma gangrenosum, Sezary's syndrome, and Behcet's disease successfully treated with oral tacrolimus but, because of their small number, they remain anecdotal at this point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…It is a hydrophobic, polycyclic lactone with powerful immunosuppressive activities 3–5 . The molecular mechanism for its anti‐inflammatory action, which is similar to that of ciclosporin, involves the inhibition of calcineurin, a calcium‐activated protein phosphatase, which is necessary for appropriate immune modulation 3–5 . Tacrolimus is used in the prevention of allograft rejection in kidney, liver and heart transplantation 3–6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a hydrophobic, polycyclic lactone with powerful immunosuppressive activities 3–5 . The molecular mechanism for its anti‐inflammatory action, which is similar to that of ciclosporin, involves the inhibition of calcineurin, a calcium‐activated protein phosphatase, which is necessary for appropriate immune modulation 3–5 . Tacrolimus is used in the prevention of allograft rejection in kidney, liver and heart transplantation 3–6 .…”
mentioning
confidence: 99%
“…The molecular mechanism for its anti‐inflammatory action, which is similar to that of ciclosporin, involves the inhibition of calcineurin, a calcium‐activated protein phosphatase, which is necessary for appropriate immune modulation 3–5 . Tacrolimus is used in the prevention of allograft rejection in kidney, liver and heart transplantation 3–6 . Additionally, systemic tacrolimus has been used in the treatment of a variety of inflammatory disorders, including psoriasis, Behçet's disease and pyoderma gangrenosum 6–9 .…”
mentioning
confidence: 99%
“…CTCLs are a heterogeneous group of lymphoproliferative disorders caused by clonally derived skin-invasive T cells. Few studies have reported the efficacy of topical tacrolimus for the treatment of CTCLs [5961]. …”
Section: Resultsmentioning
confidence: 99%
“…[45,60] Jain, et al, report a 2% incidence of skin cancer over 6.5 years in patients treated with tacrolimus. [61] Frezza, et al, reported lower incidence of all tumors in liver transplant patients treated with tacrolimus vs cyclosporine.…”
Section: Immunosuppression and Skin Cancermentioning
confidence: 99%